2010+2009×2011/2010×2011-1—2009+2008×2010/2009×2010-1
1个回答
等于 2009/2010-2008/2009-1
等于(2010-1)/2010-(2009-1)/2009-1
等于1-1/2010-1+1/2009-1
=1/2009-1/2010-1
相关问题
(2009×2010-1)/(2009+2008×2010)+(2010×2011-1)/(2010+2009×2011
[2010+2011×2009/2010×2011−1].
根号2008×2009×2010×2011+1是多少
√(2009×2010×2011×2012+1)=?
2009+2010×2008除以2009×2010-1
2011×2010-2010×2009-2010的简便方法
已知a=-2009×2009-20092008×2008+2008,b=-2010×2010-20102009×2009
2009/2010×2011=2009/2010+m求m的值
2011×2010分之2009
1/1×3+1/2×4+…1/2008×2010+1/2009×2011的结果